Inventory and Quantification of Geosites in the State Tourist Park of Alto Ribeira (PETAR, São Paulo State, Brazil) - Ferreira, Ana Rita Rodrigues [UNESP]; Lobo, Heros Augusto Santos; de Jesus Perinotto, José Alexandre [UNESP] (Springer Nature, 2019)
The territory of Brazil has a high potential for the development of geotourism, due to its natural and cultural diversity. The State Tourist Park of Alto Ribeira (PETAR) is one of the oldest protected areas in the State of São Paulo, created in 1958. The importance of the area is the result of the association between the Atlantic Rainforest with an exceptional biodiversity and karst and caves systems with a unique underground scenario. The area presents distinct tectonic environments that represent the Precambrian geological evolution of south-southeastern Brazil. The karst and caves of the PETAR were already recorded and described as an important national area to the speleological, geological, and paleontological interest, as also classified as UNESCO’s Natural Heritage and included in a proposal to the creation of a Geopark. In the present work, there were inventoried and quantified 19 geosites in the region of PETAR, most of them with speleological interest. The inventory was conducted using the following criteria: representativeness, integrity, accessibility, and scientific and esthetic value. The quantification of geosites was based on four categories of values: intrinsic value, scientific value, tourism value, and value of management. Finally, the relevance of each geosite was calculated, evidencing one geosite with international (Santana cave) and other 12 with national relevance. The conclusions raise the necessity of planning and implementing management procedures to increase the conservation and sustainable use of the analyzed geosites, despite that they are located in a natural protected area.
Keywords: Geoconservation; Geotourism; Inventory; Speleology; Vale do Ribeira